Technical Guidance for The Manufacturing Of Floating Feeds at Pokdakan Papuyu Sakti Karang Intan, Banjar District - Agussyarif Hanafie; Fatmawati Fatmawati; Muhammad Iqbal; Riska Febrianti (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2023)
Feed is the main need, which accounts for 60-70% of the total aquaculture production costs. In general, fish farming groups (Pokdakan) depend on artificial feed. High feed prices are not balanced with the selling price of fish. This is because Pokdakan does not yet understand floating feed and the operational techniques of floating feed machines. This is a problem encountered, including in Pokdakan Papuyu Sakti. So that Pokdakan Papuyu Sakti members can increase production, feed quality and the sustainability of the use of floating feed, technical guidance is needed. The aim is to increase the ability to provide quality floating feed that is sufficient for cultivation activities. The scope of solutions offered is counseling, demonstration of machine use, and making floating feed. The partners' level of knowledge and skills were evaluated based on the Guttman Scale. The evaluation results show that the introduction of machines and the manufacture of floating feed have been successfully implemented, there has been an increase in knowledge understanding > 75% or an increase of seven times from the start of the activity. The skills of Pokdakan members in carrying out the practice of making floating food increased four times.